Zagreb Architecture Guide - 100 selected buildings - Đukanović, Dubravka (Arhitektura i urbanizam, 2014)
Book review: Zagreba Architecture Guide - 100 selected buildingsAuthors:        Zlatko Karac and Alen ZunicPublishers:    UPI-2M PLUS and Facultz of Architecture of the Universitz of Zagreb